Feature selection using swarm intelligent for attacks in Ad Hoc on-demand distance verctor - Lee, Chun How, 1988-; Anazida Zainal, supervisor; Fakulti Komputeran (2014)
Thesis (Sarjana Sains Komputer (Keselamatan Maklumat)) - Universiti Teknologi Malaysia, 2014